The effect of molnupiravir and nirmatrelvir on SARS-CoV-2 genome diversity in severe models of COVID-19 - Rebekah Penrice-Randal; Eleanor G. Bentley; Parul Sharma; Adam Kirby; I'ah Donovan-Banfield; Anja Kipar; Daniele F. Mega; Chloe Bramwell; Joanne Sharp; Andrew Owen; Julian A. Hiscox; James P. Stewart (Microbiology Spectrum)
ABSTRACT Immunocompromised individuals are susceptible to severe coronavirus disease 2019 and potentially contribute to the emergence of variants with altered pathogenicity due to persistent infection. This study investigated the impact of immunosuppression on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in K18-hACE2 mice and the effectiveness of antiviral treatments in this context during the first 7 days of infection. Mice were immunosuppressed using cyclophosphamide and infected with a B lineage of SARS-CoV-2. Molnupiravir and nirmatrelvir, alone and in combination, were administered, and viral load and viral sequence diversity were assessed. Treatment of infected but immunocompromised mice with both compounds either singly or in combination resulted in decreased viral loads and pathological changes compared to untreated animals. Treatment also abrogated infection of neuronal tissue. However, no consistent changes in the viral consensus sequence were observed, except for the emergence of the S:H655Y mutation. Molnupiravir, but not nirmatrelvir or immunosuppression alone, increased the transition/transversion ratio, representative of G > A and C > U mutations, and this increase was not altered by the co-administration of nirmatrelvir with molnupiravir. Notably, immunosuppression itself did not appear to promote the emergence of mutational characteristics of variants of concern (VOCs). Further investigations are warranted to fully understand the role of immunocompromised individuals in VOC development, especially by taking persistence into consideration, and to inform optimized public health strategies. It is more likely that immunodeficiency promotes viral persistence but does not necessarily lead to substantial consensus-level changes in the absence of antiviral selection pressure. Consistent with mechanisms of action, molnupiravir showed a stronger mutagenic effect than nirmatrelvir in this model.IMPORTANCEThe central aim of this study was to risk-assess the impact of administering a mutagenic antiviral compound, molnupiravir, to patients believed to already be at risk of generating increased viral diversity, which could have severe implications for antiviral resistance development. Combination therapy has a long history of mitigating antiviral resistance risk and was used in this study to demonstrate its potential usefulness in a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) context. Animals treated with molnupiravir showed an increase in transition/transversion ratios over time, consistent with the drug’s mechanism of action and a recent UK-wide phase II clinical trial assessing the efficacy of molnupiravir in humans. The addition of nirmatrelvir increased viral clearance, which in turn reduces the probability of viral persistence and rapid intra-host evolution of SARS-CoV-2.